Ultrastructural modifications in the venom glands of workers of Apis mellifera L. (Hymenoptera : Apidae) promoted by topical application of juvenile hormone - Roat, Thaisa C.; Nocelli, Roberta C. F.; da Cruz-Landim, Carminda (Entomological Society Brasil, 2006)
The present study analyzed, the influence of the treatment with juvenile hormone on the ultrastructure of Apis mellifera L. workers' venom glands. Newly emerged workers received topical application of 1 mu l of juvenile hormone diluted in hexane, in the concentration of 2 mu g/mu l. Two controls were used; one control received no treatment (group C1) and other received topical application of 1 mu l of hexane (group C2). The aspect of the glandular cells, in not treated newly emerged workers, showed that they are not yet secreting actively. Cellular modifications happened according to the worker age and to the glandular area considered. The most active phase of the gland happened from the emergence to the 14th day. At the 25th day the cells had already lost their secretory characteristic, being the distal area the first to suffer degeneration. The treatment with juvenile hormone and hexane altered the temporal sequence of the glandular cycle, forwarding the secretory cycle and degeneration of the venom gland.
Keywords: secretory cycle; glandular degeneration; hexane; bee